Penyuluhan Hukum “Larangan Penolakan Rupiah Logam Dalam Transaksi Jual-Beli Di Kota Ternate” - Muhaimin Limatahu; Ahmad Mufti; Fathurrahim (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2022)
The purpose of carrying out community service activities (PkM) at the Faculty Level is so that buyers and traders, who are generally small traders, can get access to information and knowledge regarding the prohibition of rejecting metal rupiah money in buying and selling transactions. The method of implementing pkm at the university level is through the lecture method in the form of counseling / socialization in a blouse to small traders at the location of the implementation of PKM activities. The result of service Everyone is prohibited from refusing to accept Rupiah whose delivery is intended as payment or to settle obligations that must be fulfilled with Rupiah and/or for other financial transactions in the Territory of the Unitary State of the Republic of Indonesia, unless there is doubt about the authenticity of the Rupiah as referred to in Article 23 is punished with a maximum of 1 (one) year imprisonment and a maximum fine of Rp200,000,000, 00 (two hundred million rupiah)".